Court of swans - Dickerson, Melanie, 1970- (Dickerson, Melanie. Dericott tales, 2021)
In medieval England, after her seven brothers are falsely accused of murder and treason, eighteen-year-old Delia flees their cruel stepmother and becomes a seamstress at Westminster Palace, hoping to gain their release, with Sir Geoffrey's assistance.